Analisis Amanat Syair Lagu Pada Album “Akustichrisye” Karya Chrisye - Mastawati Ndruru (Ta'ehao: Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2022)
This research was based on by the uniqueness of song lyrics that told about the value of life, love, and message which given by author for the listener. This research was aimed to describe the message by explicit and implicit which is found in song lyrics on “Akustichrisye” album from Chrisye. The approaches and methods that is used in this research was qualitative approach with analysis method. The data research was 10 lirycs in “Akustichrisye” album from Chrisye. Research finding was shown that in lirycs of “Akustichrisye” album from Chrisye were contained two kinds of each message in lirycs that is explicit and implicit message. Based on the research finding, it was concluded that in “Akustichrisye” album from Chrisye have two kinds of message.